PENGARUH BUDAYA ORGANISASI KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN - Bayu Putra Mahardika, I Nyoman; Wibawa, I Made Artha (E-Jurnal Manajemen; Vol 8 No 1 (2019)DO - 10.24843/EJMUNUD.2019.v08.i01.p14, 2019)
The purpose of this study is to determine the influence of organizational culture, job satisfaction and organizational commitment to organizational citizenship behavior. This research was conducted at the company Focus Design Artglass Ubud. The number of samples taken as many as 67 employees, using saturated sample technique, especially simple random sampling. The data were collected through questionnaires. The analysis technique used is multiple linear regression. Based on the analysis results found that organizational culture, job satisfaction and organizational commitment have positive and significant impact on organizational citizenship behavior. The higher the organizational culture OCB will also increase, the higher the job satisfaction the higher the OCB, and the higher the organizational commitment the higher the OCB in the company Focus Design Artglass Ubud.     Keywords:       organizational culture, job satisfaction, organizational commitment, organizational citizenship behavior